2016
DOI: 10.18632/oncotarget.13579
|View full text |Cite
|
Sign up to set email alerts
|

The non-receptor tyrosine kinase TNK2/ACK1 is a novel therapeutic target in triple negative breast cancer

Abstract: Breast cancer is the most prevalent cancer in women worldwide. About 15-20% of all breast cancers do not express estrogen receptor, progesterone receptor or HER2 receptor and hence are collectively classified as triple negative breast cancer (TNBC). These tumors are often relatively aggressive when compared to other types of breast cancer, and this issue is compounded by the lack of effective targeted therapy. In our previous phosphoproteomic profiling effort, we identified the non-receptor tyrosine kinase TNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 33 publications
(42 reference statements)
1
42
1
Order By: Relevance
“…ACK1 belongs to the family of non-receptor-tyrosine-kinases and functions as a driver of tumor progression 23 , 24 . It has been documented that knockdown of ACK1 suppresses the proliferation and invasion of breast cancer cells 25 . Although several miRNAs such as miR-7 have been shown to regulate the expression of ACK1, 26 we here propose a novel miRNA regulator of ACK1.…”
Section: Discussionmentioning
confidence: 85%
“…ACK1 belongs to the family of non-receptor-tyrosine-kinases and functions as a driver of tumor progression 23 , 24 . It has been documented that knockdown of ACK1 suppresses the proliferation and invasion of breast cancer cells 25 . Although several miRNAs such as miR-7 have been shown to regulate the expression of ACK1, 26 we here propose a novel miRNA regulator of ACK1.…”
Section: Discussionmentioning
confidence: 85%
“…The SIAH2 gene is a target of estrogen/estrogen receptor (ER)-signaling and mediates the ubiquitylation of Ack1 [46]. Triple negative breast cancer (TNBC) lacks ER and exhibits a high level of Ack1 [47], which correlates with high proliferation, migration and colony formation. It has been reported that constitutive activation of Ack1 can trigger the recruitment of PI3K-independent protein kinase B (PKB, also known as AKT) to the cell membrane and subsequently activate AKT in breast cancer [48], which may be the underlying mechanism of Ack1-induced tumor progression.…”
Section: Cdc42 and Breast Cancer Cell Proliferationmentioning
confidence: 99%
“…But the nonreceptor tyrosine kinase ACK1 is activated in most aggressive TNBC cell lines. Wu et al found that inhibiting the ACK1 signal not only reduced the proliferation of TNBC cells but also promoted the invasiveness of tumor formation in xenograft mice [8]. This phenomenon indicates the dependence of TNBCs on ACK1 signal in proliferation and invasion ability.…”
Section: Ack1 and Endocrine Therapy For Breast Cancermentioning
confidence: 99%
“…Breast cancer research found that many ACK1 tyrosine kinase signaling proteins in many tumor cells are activated repeatedly [36]. ACK1 expression is positively correlated with the severity of the disease progression and negatively correlated with the survival rate in breast cancer patients [7, 8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation